2021
DOI: 10.1159/000516753
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Acute Stroke Admissions during the COVID-19 Pandemic: Data from a National Stroke Registry

Abstract: <b><i>Introduction:</i></b> The COVID-19 pandemic overwhelmed health-care systems worldwide, and medical care for other acute diseases was negatively impacted. We aimed to investigate the effect of the COVID-19 outbreak on admission rates and in-hospital care for acute stroke and transient ischemic attack (TIA) in Israel, shortly after the start of the pandemic. <b><i>Methods:</i></b> We conducted a retrospective observational study, based on data reported to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
3
19
1
Order By: Relevance
“…In aggregate, there were reductions in cardiac diagnoses and at a granular level there were reductions in atrial fibrillation as well as myocardial infarction, with potential downstream consequences, for example if fewer people with atrial fibrillation received stroke preventing anticoagulants. We observed no change in cerebral infarction strokes during the first wave, although a study in Israel found a reduction of 29% for stroke and a UK-wide registry study found only a 12% reduction in stroke admissions at the peak of the first wave [ 52 , 53 ]. Our data suggest a possible trend towards increased strokes in the last months of our analysis which, if confirmed over time, might reflect reduced opportunities for stroke prevention during the pandemic.…”
Section: Discussioncontrasting
confidence: 59%
“…In aggregate, there were reductions in cardiac diagnoses and at a granular level there were reductions in atrial fibrillation as well as myocardial infarction, with potential downstream consequences, for example if fewer people with atrial fibrillation received stroke preventing anticoagulants. We observed no change in cerebral infarction strokes during the first wave, although a study in Israel found a reduction of 29% for stroke and a UK-wide registry study found only a 12% reduction in stroke admissions at the peak of the first wave [ 52 , 53 ]. Our data suggest a possible trend towards increased strokes in the last months of our analysis which, if confirmed over time, might reflect reduced opportunities for stroke prevention during the pandemic.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, we used a Poisson regression model with robust variance as used in other studies that evaluated the impact of the COVID-19 pandemic on hospital admissions [28][29][30][31]. As mentioned, this model allowed including gender, age group, region of Brazil, the dummy variable representing the impact of the COVID-19 pandemic ("0", pre-pandemic period; "1", pandemic period) and the month of admission to control for possible seasonal variations as dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Inconvenience for patients seeking treatment might be one of the reasons for the decrease of endocrine, nutritional and metabolic diseases 13. A large proportion of hospitalised patients in this group in the paediatric department of FJMUUH were those with low-acuity diseases, such as dwarfism, sexual precocity and malnutrition, who might not draw enough attention from guardians during the pandemic period.…”
Section: Discussionmentioning
confidence: 99%